ANALYSIS OF FISHING EFFORT WITH GILL NET FISHING GEAR AT UPT COASTAL FISHERY PORT OF KUALA TUNGKAL REGENCY OF WEST TANJUNG JABUNG OF JAMBI PROVINCE - Winanda, Treza Desri; Zulkarnaini, Zulkarnaini; Hendrik, Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research is about gillnet fishing gear bisiness. was held in march 2018at UPT Fishery coastal port of Kuala Tungkal. The research objective is to find out the amount of invesment, profit and bussiness feasibility of fishing gear with ship size 6 GT and 12 GT. The method used isthe survey method with thu number ofrespondens as many 11 shipowners, census sampling method. The results of the research show that fishing business is profitable according to the criteria of the amount of invesment. Invesment (I) from a 6 GT IDR. 235.295.000/ year and 12 GT IDR. 293.460.000/year. Based on the calculation of BCR fishing bisiness catch 6 GT is 1,23and 12 GT is 1,24with BCR >1 which means that this business is profitable and feasible to continue. FRR with the calculation of net income year/ invesment multiplied 100%, then the results of FRR ship 6 GT 24,61% and ship 12 GT 23,44% larger than the interest rate at the current bank 14% and get a profit on . PPC 6 GT 4,06 for 4 years and 12 GT 4,26 for 4 year 2 months which means the greater the value of PPC the longer the time of return on investment business or the smaller the value of PPC the faster the payback period of business . Keywords: Study Analysis, Gillnet, Feasibility Study, kuala tungkal.